Preparation method of high-performance isopropyl alcohol zinc stannate sensor

By doping gold in zinc stannate and forming a heterostructure with cobalt tetroxide, the existing zinc stannate gas sensors have solved the problems of insufficient sensitivity, long response recovery time and poor stability for isopropanol detection, and high sensitivity, fast response and good stability are achieved.

CN119715702AActive Publication Date: 2025-03-28GUIZHOU ASTER NANOTECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411880724.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing zinc stannate gas sensors have problems such as insufficient sensitivity, long response recovery time and poor stability for isopropanol detection.

Method used

By doping gold into zinc stannate and forming a heterostructure with cobalt tetoxide, the preparation is performed by hydrothermal method to optimize the electronic structure and enhance the adsorption capacity and electron transport efficiency of gas molecules.

Benefits of technology

It significantly improves the response speed, sensitivity and stability of the sensor, and can efficiently detect volatile isopropanol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119715702A_ABST
    Figure CN119715702A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance isopropyl alcohol zinc stannate sensor, and belongs to the technical field of semiconductor material preparation. The invention aims to solve the problems of insufficient sensitivity, long response recovery time and poor stability of the existing zinc stannate gas sensor for detecting isopropanol. The method comprises the following steps: 1, adding cobalt nitrate and 2-methylimidazole into methanol, stirring and dissolving; 2, standing, centrifuging, carrying out suction filtration and drying; 3, sintering to obtain cobaltosic oxide; 4, preparing a zinc stannate precursor mixed solution; 5, carrying out hydrothermal reaction; 6, sintering to obtain cobaltosic oxide heterojunction zinc stannate; 7, adding cobaltosic oxide heterojunction zinc stannate and chloroauric acid into deionized water, stirring and dissolving, and then adding sodium citrate, stirring and dissolving; 8, sintering to obtain gold-doped cobaltosic oxide heterojunction zinc stannate; and 9, preparing the sensor. The method is used for preparing the high-performance isopropyl alcohol zinc stannate sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor material preparation. Background Art

[0002] Zinc stannate (ZnSnO3) is a ternary metal oxide with a perovskite structure. Its crystal structure shows a face-centered cubic arrangement, with lattice parameters a, b, and c being equal, and the three crystal plane angles α, β, and γ being 90°. In this structure, each unit cell contains four atoms, which provides stability and uniformity to the crystal. One of the characteristics of the face-centered cubic structure is the surface energy distribution of its crystal faces, where the (110) face has the highest surface energy, followed by the (100) face, and the (111) face has the lowest surface energy. This energy distribution is crucial to understanding how crystals grow and stabilize.

[0003] During the crystal growth process, the (111) faces with the lowest energy are easier to form because they represent the most energy stable form in the crystal structure. Relatively speaking, the (100) and (110) faces with higher surface energy will gradually decrease or be covered by other faces during the crystal growth process. This is the natural trend of the crystal to reach the lowest overall energy state. Ultimately, zinc stannate tends to form a stable octahedral structure. This structural feature not only reflects the basic law of crystal growth, but also provides a solid theoretical basis for the application of zinc stannate in gas sensors and other fields. Through this structural characteristic, zinc stannate can show high sensitivity and selectivity to specific gases, making it a promising candidate in the research of gas-sensitive materials.

[0004] However, the existing traditional zinc stannate gas sensors face the problems of insufficient sensitivity, long response recovery time and poor stability for isopropyl alcohol detection, which limits its application in high-demand detection fields. For example, zinc stannate-based gas sensors have low sensitivity to volatile isopropyl alcohol and slow response / recovery speed; in addition, pure zinc stannate gas sensors have disadvantages such as low isopropyl alcohol response value and poor response stability. The development of zinc stannate gas sensors with high sensitivity, fast response and high stability is of great significance to meet the market demand for high-performance gas detection technology. Summary of the invention

[0005] The invention aims to solve the problems of insufficient sensitivity, long response recovery time and poor stability of the existing zinc stannate gas sensor for detecting isopropyl alcohol, and further provides a method for preparing a high-performance isopropyl alcohol zinc stannate sensor.

[0006] A method for preparing a high-performance zinc isopropylate stannate sensor is carried out according to the following steps:

[0007] 1. Add cobalt nitrate and 2-methylimidazole into methanol and stir to dissolve to obtain a precursor mixed solution;

[0008] 2. The precursor mixed solution is allowed to stand to form a precipitate, and then centrifuged, filtered and dried in sequence to obtain a precursor solid product;

[0009] 3. grinding and sintering the precursor solid product to obtain cobalt tetroxide;

[0010] 4. adding crystalline tin tetrachloride, zinc acetate, sodium hydroxide and cobalt tetroxide into deionized water and stirring to dissolve, thereby obtaining a zinc stannate precursor mixed solution;

[0011] 5. subjecting the zinc stannate precursor mixed solution to a hydrothermal reaction, and then sequentially centrifuging, filtering and drying to obtain a zinc stannate solid product;

[0012] 6. Grinding and sintering the zinc stannate solid product to obtain cobalt trioxide heterojunction zinc stannate;

[0013] 7. Add cobalt tetraoxide heterojunction zinc stannate and tetrachloroauric acid into deionized water, stir and dissolve, then ultrasonicate, add sodium citrate, stir and dissolve, and finally centrifuge, filter and dry in sequence to obtain a solid product;

[0014] 8. grinding and sintering the solid product to obtain gold-doped cobalt tetroxide heterojunction zinc stannate;

[0015] 9. The gold-doped cobalt tetroxide heterojunction zinc stannate is dissolved and coated on the electronic components of the gas sensor, and then calcined and aged after drying to obtain the gold-doped cobalt tetroxide heterojunction zinc stannate gas sensor.

[0016] The beneficial effects of the present invention are:

[0017] 1. In the present invention, the heterostructure formed by gold-doped zinc stannate and cobalt oxide is the key to improving gas-sensitive performance. The doping of gold atoms not only optimizes the electronic structure of zinc stannate, thereby enhancing the adsorption capacity of gas molecules, but also reduces the activation energy required for gas-sensitive reactions. At the same time, cobalt oxide, as a material with high catalytic activity and high specific surface area, forms a heterostructure with zinc stannate, which further enhances the gas-sensitive performance of the material. This heterostructure not only improves the material's adsorption capacity for gas molecules, but also promotes the transmission of electrons, thereby improving the response speed and sensitivity of the sensor.

[0018] 2. The present invention adopts a hydrothermal method to prepare a gold-doped zinc stannate and cobalt oxide heterostructure, which is simple, low-cost and highly repeatable. Using a gold compound as a dopant and mixing it with deionized water, the uniform distribution of gold atoms in the zinc stannate lattice is achieved, thereby significantly improving the gas-sensing performance of the material. This heterostructure enhances the gas adsorption capacity and electron transmission efficiency, improves the response speed and sensitivity of the sensor, and provides a new and effective way to prepare high-performance gas sensors.

[0019] The invention is used for a method for preparing a high-performance isopropyl alcohol zinc stannate sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A comparison chart of the sensitivity of the ZnSnO3 sensor prepared in the comparative experiment and the Au-Co3O4@ZnSnO3 sensor prepared in Example 1 in isopropanol gas detection;

[0021] Figure 2 This is a test chart of the repeatability of the Au-Co3O4@ZnSnO3 sensor prepared in Example 1 for isopropanol gas detection;

[0022] Figure 3 This is a graph showing the long-term effectiveness of the Au-Co3O4@ZnSnO3 sensor prepared in Example 1 for isopropanol gas detection;

[0023] Figure 4 This is a test diagram of the response-recovery time of the Au-Co3O4@ZnSnO3 sensor prepared in Example 1 to isopropanol gas detection;

[0024] Figure 5 X-ray diffraction (XRD) patterns of Au-Co3O4@ZnSnO3 prepared in step eight of Example 1 and ZnSnO3 prepared in step three of the comparative experiment;

[0025] Figure 6 The Raman spectra of Co3O4 prepared in step 3 of Example 1, Au-Co3O4@ZnSnO3 prepared in step 8 of Example 1, and ZnSnO3 prepared in step 3 of the comparative experiment;

[0026] Figure 7 The microstructure of ZnSnO3 prepared in step 3 of the comparative experiment;

[0027] Figure 8 This is the microstructure diagram of Au-Co3O4@ZnSnO3 prepared in step eight of Example 1. DETAILED DESCRIPTION

[0028] Specific implementation method 1: This implementation method is a method for preparing a high-performance isopropyl alcohol zinc stannate sensor, which is carried out according to the following steps:

[0029] 1. Add cobalt nitrate and 2-methylimidazole into methanol and stir to dissolve to obtain a precursor mixed solution;

[0030] 2. The precursor mixed solution is allowed to stand to form a precipitate, and then centrifuged, filtered and dried in sequence to obtain a precursor solid product;

[0031] 3. grinding and sintering the precursor solid product to obtain cobalt tetroxide;

[0032] 4. adding crystalline tin tetrachloride, zinc acetate, sodium hydroxide and cobalt tetroxide into deionized water and stirring to dissolve to obtain a zinc stannate precursor mixed solution;

[0033] 5. subjecting the zinc stannate precursor mixed solution to a hydrothermal reaction, and then sequentially centrifuging, filtering and drying to obtain a zinc stannate solid product;

[0034] 6. Grinding and sintering the zinc stannate solid product to obtain cobalt trioxide heterojunction zinc stannate;

[0035] 7. Add cobalt tetraoxide heterojunction zinc stannate and tetrachloroauric acid into deionized water, stir and dissolve, then ultrasonicate, add sodium citrate, stir and dissolve, and finally centrifuge, filter and dry in sequence to obtain a solid product;

[0036] 8. grinding and sintering the solid product to obtain gold-doped cobalt tetroxide heterojunction zinc stannate;

[0037] 9. The gold-doped cobalt tetroxide heterojunction zinc stannate is dissolved and coated on the electronic components of the gas sensor, and then calcined and aged after drying to obtain the gold-doped cobalt tetroxide heterojunction zinc stannate gas sensor.

[0038] The sintering in step six of this specific embodiment mainly promotes the crystal transformation and phase purification of the precursor material through heat treatment, forming a cobalt tetroxide heterojunction zinc stannate structure with a specific crystal form, while enhancing the interface bonding between the two materials, forming a built-in electric field, promoting the separation and migration of carriers, and improving the catalytic activity of the material, thereby optimizing the performance of the gas sensor.

[0039] In this specific embodiment, an appropriate amount of gold doping can significantly improve the gas-sensing performance of zinc stannate because gold doping can promote the reactivity of the grain surface, improve the dispersion between grains, and form a uniform pore structure, thereby enhancing the adsorption capacity of gas molecules.

[0040] In addition, the construction of metal oxide heterojunctions is also an effective strategy to improve gas sensing performance. Heterostructures can form a built-in electric field, promote the rapid separation of photogenerated carriers, and extend the carrier lifetime, thereby improving gas sensing performance. The heterostructure formed by gold-doped zinc stannate and cobalt tetroxide increases the active sites of the material, thereby optimizing the gas sensing performance.

[0041] In summary, this specific embodiment successfully prepared a material with excellent gas sensing performance by precisely controlling the amount of gold doping and constructing a heterostructure of zinc stannate and cobalt oxide. This material exhibits high sensitivity, rapid response and good stability when detecting volatile isopropyl alcohol, providing a new idea for the preparation of high-performance gas sensors.

[0042] The beneficial effects of this embodiment are:

[0043] 1. In this embodiment, the heterostructure formed by gold-doped zinc stannate and cobalt oxide is the key to improving gas-sensitive performance. The doping of gold atoms not only optimizes the electronic structure of zinc stannate, thereby enhancing the adsorption capacity of gas molecules, but also reduces the activation energy required for gas-sensitive reactions. At the same time, cobalt oxide, as a material with high catalytic activity and high specific surface area, forms a heterostructure with zinc stannate, which further enhances the gas-sensitive performance of the material. This heterostructure not only improves the material's adsorption capacity for gas molecules, but also promotes the transmission of electrons, thereby improving the response speed and sensitivity of the sensor.

[0044] 2. This embodiment adopts a hydrothermal method to prepare a gold-doped zinc stannate and cobalt oxide heterostructure, which is simple, low-cost and highly repeatable. Using a gold compound as a dopant and mixing it with deionized water, the uniform distribution of gold atoms in the zinc stannate lattice is achieved, thereby significantly improving the gas-sensing performance of the material. This heterostructure enhances the gas adsorption capacity and electron transmission efficiency, improves the response speed and sensitivity of the sensor, and provides a new and effective way to prepare high-performance gas sensors.

[0045] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the molar ratio of cobalt nitrate to 2-methylimidazole in step 1 is 1:(2-10); the volume ratio of cobalt nitrate to methanol in step 1 is 1 mol:(10-30) L. Others are the same as specific embodiment 1.

[0046] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: in step two, the precursor mixed solution is left to stand for 15h to 30h to form a precipitate; the centrifugation, suction filtration and drying described in step two, step five and step seven are specifically carried out according to the following steps: centrifugation for 5min to 20min at a speed of 3000r / min to 5000r / min, then suction filtration under the condition of washing with detergent, and finally drying for 8h to 24h at a temperature of 40℃ to 100℃; the detergent described in step two is anhydrous ethanol; the detergent described in step five and step seven is deionized water and anhydrous ethanol used alternately. The rest is the same as specific implementation method one or two.

[0047] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the sintering described in step 3 is specifically carried out according to the following steps: placing in a tube furnace, heating to 300°C to 700°C at a heating rate of 0.6°C / min to 1.5°C / min, and then sintering at a temperature of 300°C to 700°C for 60min to 150min. The rest is the same as specific embodiments 1 to 3.

[0048] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the molar ratio of the crystallized tin tetrachloride to zinc acetate in step 4 is 1:(0.5-2); the molar ratio of the crystallized tin tetrachloride to sodium hydroxide in step 4 is 1:(5-10); the molar ratio of the crystallized tin tetrachloride to cobalt oxide in step 4 is 1:(0.01-0.1); the volume ratio of the crystallized tin tetrachloride to deionized water in step 4 is 1 mol:(5-20) L. The rest is the same as specific embodiments 1 to 4.

[0049] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the hydrothermal reaction described in step 5 is specifically carried out according to the following steps: placing in a high pressure reactor, heating to 100°C to 200°C at a heating rate of 3°C / min to 10°C / min, and hydrothermally reacting at a temperature of 100°C to 200°C for 12h to 20h. Others are the same as specific embodiments 1 to 5.

[0050] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that the sintering described in step 6 is specifically carried out according to the following steps: placing in a muffle furnace, heating to 400°C to 500°C at a heating rate of 3°C / min to 10°C / min, and sintering at a temperature of 400°C to 500°C for 1h to 3h. Others are the same as specific embodiments 1 to 6.

[0051] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the molar ratio of the cobalt trioxide heterojunction zinc stannate to tetrachloroauric acid described in step seven is 1:(0.001-0.01); the molar ratio of the tetrachloroauric acid to sodium citrate described in step seven is 1:(1-5); the volume ratio of the mole of the cobalt trioxide heterojunction zinc stannate described in step seven to deionized water is 1 mol:(15-50) L. The rest is the same as specific embodiments one to seven.

[0052] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that the sintering described in step 8 is specifically carried out according to the following steps: placing in a muffle furnace, heating to 200°C to 400°C at a heating rate of 3°C / min to 10°C / min, and sintering for 30min to 70min at a temperature of 200°C to 400°C. Others are the same as specific embodiments 1 to 8.

[0053] Specific implementation ten: This implementation is different from one of specific implementations one to nine in that: in step nine, gold-doped cobalt oxide heterojunction zinc stannate is dissolved in a solvent to obtain a slurry, and the slurry is coated on the electronic components of the gas sensor; the solvent is ether, methanol or ethanol; the mass percentage of gold-doped cobalt oxide heterojunction zinc stannate in the slurry is 30% to 70%; the drying described in step nine is specifically dried at a temperature of 60°C to 120°C; the calcination described in step nine is specifically calcined at a temperature of 150°C to 200°C for 1h to 3h; the aging described in step nine is specifically aged for 48h to 144h under a current of 50mA to 120mA. The rest is the same as specific implementations one to nine.

[0054] The following examples are used to verify the beneficial effects of the present invention:

[0055] Embodiment 1:

[0056] A method for preparing a high-performance zinc isopropylate stannate sensor is carried out according to the following steps:

[0057] 1. Add cobalt nitrate and 2-methylimidazole into methanol, stir for 60 minutes at a temperature of 25°C and a stirring speed of 400 r / min to obtain a precursor mixed solution;

[0058] The molar ratio of the cobalt nitrate to 2-methylimidazole is 1:8; the volume ratio of the cobalt nitrate to methanol is 1 mol:25L;

[0059] 2. The precursor mixed solution was allowed to stand for 24 hours to form a precipitate, and then centrifuged at a speed of 3000 r / min for 10 minutes, and then filtered under anhydrous ethanol washing, and finally dried at a temperature of 80°C for 12 hours to obtain a precursor solid product;

[0060] 3. Grind the solid product of the precursor, place it in a tube furnace, heat it to 500°C at a heating rate of 1°C / min, and then sinter it at 500°C for 2h to obtain cobalt tetroxide (Co3O4);

[0061] 4. Add crystalline tin tetrachloride, zinc acetate, sodium hydroxide and cobalt tetroxide into deionized water, stir for 20 minutes at a temperature of 25° C. and a stirring speed of 400 r / min to obtain a zinc stannate precursor mixed solution;

[0062] The molar ratio of the crystalline tin tetrachloride to zinc acetate is 1:1; the molar ratio of the crystalline tin tetrachloride to sodium hydroxide is 1:10; the molar ratio of the crystalline tin tetrachloride to cobalt oxide is 1:0.017; the volume ratio of the crystalline tin tetrachloride to deionized water is 1 mol:10L;

[0063] 5. The zinc stannate precursor mixed solution is placed in a high-pressure reactor, and the temperature is raised to 140°C at a heating rate of 5°C / min. The mixture is subjected to a hydrothermal reaction at 140°C for 12 hours, and then centrifuged at a speed of 3000r / min for 10 minutes. The mixture is then filtered under alternate washing with deionized water and anhydrous ethanol, and finally dried at 80°C for 12 hours to obtain a zinc stannate solid product.

[0064] 6. Grind the zinc stannate solid product, place it in a muffle furnace, heat it to 500°C at a heating rate of 5°C / min, and sinter it at 500°C for 2h to obtain cobalt oxide heterojunction zinc stannate (Co3O4@ZnSnO3);

[0065] 7. Add cobalt tetraoxide heterojunction zinc stannate and tetrachloroauric acid to deionized water, stir for 10 minutes at a temperature of 25°C and a stirring speed of 400 r / min, then ultrasonically treat for 10 minutes at a frequency of 40 kHz, add sodium citrate, stir for 60 minutes at a temperature of 25°C and a stirring speed of 400 r / min, then centrifuge for 10 minutes at a speed of 3000 r / min, then filter under alternating washing with deionized water and anhydrous ethanol, and finally dry at a temperature of 80°C for 12 hours to obtain a solid product;

[0066] The molar ratio of the cobalt trioxide heterojunction zinc stannate to tetrachloroauric acid is 1:0.003; the molar ratio of the tetrachloroauric acid to sodium citrate is 1:3; the volume ratio of the cobalt trioxide heterojunction zinc stannate to deionized water is 1 mol:30L;

[0067] 8. Grind the solid product, place it in a muffle furnace, heat it to 350° C. at a heating rate of 5° C. / min, and sinter it at 350° C. for 60 minutes to obtain gold-doped cobalt tetroxide heterojunction zinc stannate (Au-Co3O4@ZnSnO3);

[0068] 9. Dissolve gold-doped cobalt tetroxide heterojunction zinc stannate in a solvent to obtain a slurry, apply the slurry on an Al2O3 ceramic tube, dry at 80°C, calcine at 200°C for 2h, weld to a sensor base after calcination, and then age for 120h at a current of 80mA to obtain a gold-doped cobalt tetroxide heterojunction zinc stannate gas sensor, i.e., Au-Co3O4@ZnSnO3 sensor;

[0069] The solvent is ethanol; the mass percentage of gold-doped cobalt tetroxide heterojunction zinc stannate in the slurry is 50%.

[0070] Comparative experiment:

[0071] 1. Add crystalline tin tetrachloride, zinc acetate and sodium hydroxide into deionized water, stir for 20 minutes at a temperature of 25°C and a stirring speed of 400 r / min to obtain a mixed solution;

[0072] The molar ratio of the crystalline tin tetrachloride to zinc acetate is 1:1; the molar ratio of the crystalline tin tetrachloride to sodium hydroxide is 1:10; the volume ratio of the crystalline tin tetrachloride to deionized water is 1 mol:10L;

[0073] 2. The mixed solution was placed in a high-pressure reactor, and the mixture was subjected to a hydrothermal reaction at a temperature of 140°C for 12 hours. After the hydrothermal treatment, the mixture was centrifuged at a speed of 3000 rpm for 10 minutes, and then filtered under alternate washing with deionized water and anhydrous ethanol. Finally, the mixture was dried at a temperature of 80°C for 12 hours to obtain a solid product.

[0074] 3. Grind the solid product, then place it in a muffle furnace and sinter it at 500°C for 2 hours to obtain pure zinc stannate (ZnSnO3);

[0075] Fourth, pure zinc stannate was dissolved in a solvent to obtain a slurry, the slurry was coated on an Al2O3 ceramic tube, dried at 80°C, calcined at 200°C for 2h, welded to the sensor base after calcination, aged for 120h at a current of 80mA, and a pure zinc stannate gas sensor, i.e., a ZnSnO3 sensor, was obtained;

[0076] The solvent is ethanol; the mass percentage of pure zinc stannate in the slurry is 50%.

[0077] Gas-sensing performance test: The test is carried out by the static gas distribution method, and the device is heated to 260°C using a resistance wire. The sensitivity calculation formula is S=Ra / Rg, where Rg and Ra represent the resistance values ​​of the sensor when it reaches a stable state in the test gas and pure air respectively. Figure 1 The sensitivity comparison chart of the ZnSnO3 sensor prepared in the comparative experiment and the Au-Co3O4@ZnSnO3 sensor prepared in Example 1 in isopropanol gas detection is shown in the figure. As can be seen from the figure, at a concentration of 100ppm isopropanol, the sensitivity value of the Au-Co3O4@ZnSnO3 gas sensor is about 90, while the sensitivity value of the undoped pure zinc stannate sensor is about 25, indicating that the performance after doping is significantly improved by about 3.6 times.

[0078] Repeatability test process: First, fix the gas sensor in the test instrument and ensure the sealing of the test environment. Test at a device temperature of 260°C. After the experiment starts, after 100 seconds, introduce isopropyl alcohol gas with a concentration of 100ppm into the test environment. Continue to maintain this gas concentration until the end of the next 100 seconds. Then, open the sealing cover and expose the sensor to the outside air to remove residual gas and reset its state. This continuous process, from gas introduction to sensor exposure to air, is defined as a complete test cycle. Perform 5 cycles of testing continuously. Figure 2 This is a repeatability test diagram of the Au-Co3O4@ZnSnO3 sensor prepared in Example 1 for isopropanol gas detection; as can be seen from the figure, the isopropanol gas concentration is 100ppm. After five cycles of cyclic testing, the sensitivity and response recovery curve of the material show good stability, and the sensitivity still reaches 87 after the fifth cycle test. This result shows that the gas sensor prepared by Au-Co3O4@ZnSnO3 material has excellent repeatability in the isopropanol gas environment and can continuously and effectively perform gas detection.

[0079] Long-term test process: The Au-Co3O4@ZnSnO3 gas sensor was tested 11 times in 21 days, once every other day, that is, on days 1, 3, 5, 7, 9, 11, 13, 15, 17, 19, and 21 of the 21 days. The single test method is a complete cycle of the above repetitive test. When not tested, the device is in the air, and isopropyl alcohol gas is introduced only during the test. Figure 3 This is a long-term graph of the Au-Co3O4@ZnSnO3 sensor prepared in Example 1 for isopropanol gas detection; as can be seen from the figure, after 11 tests over a period of 21 days, the isopropanol gas concentration was 100ppm and its sensitivity could be maintained at a high level (sensitivity was 82-93). This result shows that the Au-Co3O4@ZnSnO3 material has good stability for the detection of isopropanol gas.

[0080] Figure 4 This is a response-recovery time test diagram of the Au-Co3O4@ZnSnO3 sensor prepared in Example 1 for isopropanol gas detection; as can be seen from the figure, in an isopropanol gas environment with a concentration of 100ppm, the response time of the material is 23.4s and the recovery time is 8.2s.

[0081] Figure 5 X-ray diffraction (XRD) patterns of Au-Co3O4@ZnSnO3 prepared in step eight of Example 1 and ZnSnO3 prepared in step three of the comparative experiment. The XRD diffraction peaks of the sintered samples show an obvious broadening phenomenon, which is usually associated with a decrease in the crystallinity of the sample. Compared with the XRD pattern of pure zinc stannate, the main peak at 32° of the XRD pattern of Au-Co3O4@ZnSnO3 shows sharpening, and a new diffraction peak is observed at 37°. Both changes are attributed to the formation of the Co3O4@ZnSnO3 heterostructure. No independent diffraction peaks of the gold (Au) element were observed in the XRD pattern, which may be due to the excessive broadening of the diffraction peaks, which causes the diffraction peaks of gold to be masked, and thus cannot be clearly distinguished in the spectrum.

[0082] Figure 6 The Raman spectra of Co3O4 prepared in step 3 of Example 1, Au-Co3O4@ZnSnO3 prepared in step 8 of Example 1, and ZnSnO3 prepared in step 3 of the comparative experiment are shown in Figure 1. The characteristic peak of the Raman spectrum of cobalt tetroxide is located at 194 cm -1 、482cm -1 、522cm -1 、618cm -1 and 691cm -1By comparing the spectral data of the cobalt oxide prepared in step 3 of Example 1 with the standard Raman spectrum of cobalt oxide, no obvious impurity characteristic peaks were observed, which confirmed that the cobalt oxide prepared in step 3 of Example 1 had high purity. By comparing the Raman spectra of Au-Co3O4@ZnSnO3 with that of pure ZnSnO3, it can be clearly observed that Au-Co3O4@ZnSnO3 has a peak at 482cm -1 and 522cm -1 The additional Raman peaks appeared at the 40°C, which confirmed the successful preparation of the Co3O4@ZnSnO3 heterostructure. In addition, the Raman peaks of the Au-Co3O4@ZnSnO3 sample showed a slight frequency shift compared to pure ZnSnO3, which was attributed to the lattice distortion and electronic structure adjustment introduced by gold (Au) doping. These observations indicate that gold doping has an effect on the Raman spectral properties of the material, thus confirming the successful synthesis of the Au-Co3O4@ZnSnO3 composite material and its structural characteristics.

[0083] Figure 7 The microstructure of ZnSnO3 prepared in step 3 of the comparative experiment; Figure 8 This is the microstructure of Au-Co3O4@ZnSnO3 prepared in step eight of Example 1; Figure 7 In the experiment, the surface of pure ZnSnO3 grains showed smooth texture and obvious edges and corners, but the dispersion and size distribution of grains showed certain heterogeneity. Figure 8 The crystal surface of the Au-Co3O4@ZnSnO3 composite material in the experiment showed a more significant decomposition phenomenon, which led to an increase in surface roughness and subsequently increased the specific surface area of ​​the material. In addition, the crystal dispersion of the composite material was significantly improved, forming a uniform pore structure, which is extremely beneficial for enhancing gas adsorption performance.

Claims

1. A method for preparing a high-performance isopropyl zinc stannate sensor, characterized in that It is carried out in the following steps:

1. Add cobalt nitrate and 2-methylimidazole into methanol and stir to dissolve to obtain a precursor mixed solution; 2. The precursor mixed solution is allowed to stand to form a precipitate, and then centrifuged, filtered and dried in sequence to obtain a precursor solid product; 3. grinding and sintering the precursor solid product to obtain cobalt tetroxide; 4. adding crystalline tin tetrachloride, zinc acetate, sodium hydroxide and cobalt tetroxide into deionized water and stirring to dissolve to obtain a zinc stannate precursor mixed solution; 5. subjecting the zinc stannate precursor mixed solution to a hydrothermal reaction, and then sequentially centrifuging, filtering and drying to obtain a zinc stannate solid product; 6. Grinding and sintering the zinc stannate solid product to obtain cobalt trioxide heterojunction zinc stannate; 7. Add cobalt tetraoxide heterojunction zinc stannate and tetrachloroauric acid into deionized water, stir and dissolve, then ultrasonicate, add sodium citrate, stir and dissolve, and finally centrifuge, filter and dry in sequence to obtain a solid product; 8. grinding and sintering the solid product to obtain gold-doped cobalt tetroxide heterojunction zinc stannate; 9. The gold-doped cobalt tetroxide heterojunction zinc stannate is dissolved and coated on the electronic components of the gas sensor, and then calcined and aged after drying to obtain the gold-doped cobalt tetroxide heterojunction zinc stannate gas sensor.

2. The method for preparing a high-performance zinc isopropyl stannate sensor according to claim 1, characterized in that The molar ratio of the cobalt nitrate to 2-methylimidazole in step 1 is 1:(2-10); the volume ratio of the cobalt nitrate to methanol in step 1 is 1 mol:(10-30)L.

3. The method for preparing a high-performance zinc isopropyl stannate sensor according to claim 1, characterized in that In step 2, the precursor mixed solution is allowed to stand for 15h to 30h to form a precipitate; the centrifugation, filtration and drying described in step 2, step 5 and step 7 are specifically carried out according to the following steps: centrifugation for 5min to 20min at a rotation speed of 3000r / min to 5000r / min, then filtration under the condition of washing with detergent, and finally drying for 8h to 24h at a temperature of 40℃ to 100℃; the detergent described in step 2 is anhydrous ethanol; the detergent described in step 5 and step 7 is deionized water and anhydrous ethanol used alternately.

4. The method for preparing a high-performance zinc isopropyl stannate sensor according to claim 1, characterized in that The sintering described in step three is specifically carried out according to the following steps: placing in a tubular furnace, heating to 300°C to 700°C at a heating rate of 0.6°C / min to 1.5°C / min, and then sintering at a temperature of 300°C to 700°C for 60min to 150min.

5. The method for preparing a high-performance zinc isopropyl stannate sensor according to claim 1, characterized in that The molar ratio of the crystalline tin tetrachloride described in step 4 to zinc acetate is 1:(0.5-2); the molar ratio of the crystalline tin tetrachloride described in step 4 to sodium hydroxide is 1:(5-10); the molar ratio of the crystalline tin tetrachloride described in step 4 to cobalt oxide is 1:(0.01-0.1); the volume ratio of the mole of the crystalline tin tetrachloride described in step 4 to deionized water is 1 mol:(5-20)L.

6. The method for preparing a high-performance zinc isopropyl stannate sensor according to claim 1, characterized in that The hydrothermal reaction described in step five is specifically carried out according to the following steps: placing in a high pressure reactor, heating to 100°C to 200°C at a heating rate of 3°C / min to 10°C / min, and performing the hydrothermal reaction at a temperature of 100°C to 200°C for 12h to 20h.

7. The method for preparing a high-performance zinc isopropyl stannate sensor according to claim 1, characterized in that The sintering described in step six is ​​specifically carried out according to the following steps: placing in a muffle furnace, heating to 400°C to 500°C at a heating rate of 3°C / min to 10°C / min, and sintering at a temperature of 400°C to 500°C for 1h to 3h.

8. The method for preparing a high-performance zinc isopropyl stannate sensor according to claim 1, characterized in that The molar ratio of the cobalt oxide heterojunction zinc stannate to tetrachloroauric acid described in step seven is 1:(0.001-0.01); the molar ratio of the tetrachloroauric acid to sodium citrate described in step seven is 1:(1-5); the volume ratio of the mole of the cobalt oxide heterojunction zinc stannate described in step seven to deionized water is 1 mol:(15-50)L.

9. The method for preparing a high-performance zinc isopropyl stannate sensor according to claim 1, characterized in that The sintering described in step eight is specifically carried out according to the following steps: placing in a muffle furnace, heating to 200°C to 400°C at a heating rate of 3°C / min to 10°C / min, and sintering at a temperature of 200°C to 400°C for 30min to 70min.

10. The method for preparing a high-performance zinc isopropyl stannate sensor according to claim 1, characterized in that In step nine, gold-doped cobalt tetroxide heterojunction zinc stannate is dissolved in a solvent to obtain a slurry, and the slurry is coated on the electronic components of the gas sensor; the solvent is ether, methanol or ethanol; the mass percentage of gold-doped cobalt tetroxide heterojunction zinc stannate in the slurry is 30% to 70%; the drying described in step nine is specifically drying at a temperature of 60°C to 120°C; the calcining described in step nine is specifically calcining at a temperature of 150°C to 200°C for 1h to 3h; the aging described in step nine is specifically aging for 48h to 144h under a current of 50mA to 120mA.

Citation Information

Patent Citations

  • Cobalt tetroxide / zinc oxide nanoflower heterojunction film sensitive to acetone

    CN110749628A

  • Preparation method of Au-loaded zinc tin oxide composite material triethylamine gas sensor

    CN115290707A

  • ZnSnO3 / ZnO nano composite material and application thereof in formaldehyde detection

    CN116891250A

  • Complex frame Fe-ZnO material and preparation method and application thereof

    CN118387913A

  • Preparation method, product and application of gold-loaded zinc stannate gas-sensitive material

    CN118501214A